Protocol for Projecting Allele Frequency Change under Future Climate Change at Adaptive-Associated Loci - Meghan Blumstein; Andrew Richardson; David Weston; Jin Zhang; Wellington Muchero; Robin Hopkins (STAR Protocols, 2020)
Summary: We describe how to predict population-level allele frequency change at loci associated with locally adapted traits under future climate conditions. Our method can identify populations that are at higher risk of local extinction and those that might be prime targets for conservation intervention. We draw on previously developed community ecology statistical methods and apply them in novel ways to plant genomes. While a powerful diagnostic tool, our method requires a wealth of genomic data for use.For complete details on the use and execution of this protocol, please refer to Blumstein et al. (2020).